Repmod : A Smaller Sibling for Multimod - Meredith, Guy. (Washington, D.C. : International Monetary Fund, 1999)
This paper describes a small macroeconomic model based on a representative industrial-country block of MULTIMOD, the IMF's multi-country simulation model. REPMOD is designed to provide a more flexible and accessible tool for analysis by individual country desks than the full version of MULTIMOD. It also allows the construction of model-consistent baseline paths, in addition to conventional shock-minus-control experiments. After discussing the model's general structure and properties, some distinctive aspects are illustrated via simulations that explore the implications of Japan's liquidity trap.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet